Prevalence of Overweight, Obesity and Risk of Coronary Pathy in Jurisdictions of the State of Rondônia – Brazil - de Almeida, Helio Franklin Rodrigues; Silva, André Ribeiro da; Queiroz, Lucicleia Barreto; Neto, Leonardo Severo da Luz; Paraguassu Chaves, Carlos Alberto; Assis, Artur Felipe Queiroz; Casseb, Almeida Andrade (International Journal of Advanced Engineering Research and Science, 2021)
The aim of this study was to investigate the prevalence of overweight, obesity and risk of coronary artery disease in judges in the State of Rondônia, Brazil. The sample consisted of 23 subjects in work activity in the court of justice of the state of Rondônia, aged from 28 to 45 years, who were divided into two groups of studies, according to age: Study Group 1 (GE-1 ), composed of 10 subjects from 28 to 36 years of age (Age: 33.6 ± 2.91; Body weight: 77.27 ± 9.85; Height: 170.1 ± 7.47); and b) Study Group 2 (GE-2) ,composed of 13 subjects from 37 to 45 years of age (Age: 42.4 ± 2.53; Body weight: 80.76 ± 8.14; Height: 155.3 ± 16.40). To detect possible significant differences between the scores related to physical characteristics and the study variables of GE-1 and Ge-2, descriptive statistics and Student's "t" test were used for independent samples, respectively, seeking a significance of p<0.05. The scores of the analyzed variables did not present, when compared to each other, statistical differences at the level of p<0.05, with a p=0.313 for the EG-1 BMI and a p=0.313 for the risk of coronary artery disease in EG-2. = 0.236. It was also verified that the mean values of the aforementioned variable (27.4 kg/m 2 and 28.7 kg/m 2for EG-1 and EG-2, respectively), they are classified as "overweight", and when quantified in percentage it was noticed that 20% of the subjects in EG-1 have a BMI classified as "normal", 60% have " overweight" and 20% are "obese", and in EG-2 individuals only 7.8% have a BMI classified as "normal", 61.5% are "overweight" and 30.7% are "obese" . Regarding the risk of coronary artery disease (CR), it appears that in EG-1 70% of the sample has it classified as "high", 10% classified as "low", 10% bandaged as "medium", and 10% as presents as “very high”. IN GE-2, no element has the RC classified as “low”, being 77% classified as “high”, 11.5% as “medium”, and 11.5% as “very high”. These results indicate that the combination of different risk behaviors such as: smoking.